Socialization of Savings and Loan Law to Increase Public Understanding at the Darussalam Sako Council in Palembang City - Bagus Setiawan; Ria Astina; Cindi Pramita (Sean Institute, 2026)
The lack of public understanding regarding savings and loans based on Sharia principles can lead to transaction practices that are not in accordance with Islamic law. Therefore, this community service activity aims to improve public understanding of savings and loans based on Sharia Economic Law. The activity was held on June 13, 2026, at the Darussalam Assembly, Jalan Nusantara 2, Lekipali Village, Sako District, Palembang City, and involved 25 participants. The methods used included lectures, discussions, and a question-and-answer session. The material covered the concept of savings and loans, the qardh contract, the prohibition of usury, and the legal basis for them in Islam. The activity went well and received a positive response from participants who actively participated in the discussion and asked questions related to savings and loans in their daily lives. Through this activity, participants gained a better understanding of the importance of implementing savings and loans transactions in accordance with Sharia principles. This activity is expected to increase literacy in Sharia Economic Law and encourage the public to adopt fair, transparent, and usury-free financial practices..